Tracking and vertexing with a thin CMOS pixel beam telescope - Battaglia, M; Bisello, D; Bolla, G; Bortoletto, D; Contarato, D; Franchino, S; Giubilato, P; Glesener, L; Hooberman, B; Pantano, D (2008)
We present results of a study of charged particle track and vertex reconstruction with a beam telescope made of four layers of 50 μ m-thin CMOS monolithic pixel sensors using the 120 GeV protons at the FNAL Meson Test Beam Facility. We compare our results to the performance requirements of a future e+ e- linear collider in terms of particle track extrapolation and vertex reconstruction accuracies. © 2008 Elsevier B.V. All rights reserved.